Estimation of HIV-testing rates to maximize early diagnosis-derived benefits at the individual and population level - Dilernia, Dario Alberto (2013)
In HIV infection, initiation of treatment is associated with improved clinical outcom and reduced rate of sexual transmission. However, difficulty in detecting infection in early stages impairs those benefits. We determined the minimum testing rate that maximizes benefits derived from early diagnosis.